English Language Learning in Encouraging the Aviation Security: Case Study at Vocational Training Program - Maya Masita; Muhammad Basri; Amirullah Abduh; Saptandri Widiyanto; Ahmad Rossydi; Anugerah Febrian Syam (Journal of Vocational Education Studies, 2026)
Indonesian Language is playing a crucial role as a unifying tool and the official language for government communications as stated at Article 36 of the 1945 Constitution of Indonesia. However, the International Civil Aviation Organization (ICAO) designates six official languages: French, English, Spanish, Russian, Arabic, and Chinese, to facilitate communication among its 193 member states. This study employs a qualitative design, utilizing document analysis and interviews to explore the potential strategies for improving English language proficiency in the aviation sector. The results indicate that to enhance English proficiency among aviation personnel in Indonesia, tailored ESP Programs, simulation-based training, regular assessments, and blended learning approaches should be implemented. Collaborations with international organizations and support from the government will further ensure alignment with ICAO standards, fostering effective communication in critical situations. The discussion highlights the importance of English proficiency at Indonesian airports for providing directions and services, in compliance with Indonesia's ratification of ICAO's six languages. This study recommends some potential strategies to strengthening English language education in Indonesia's aviation sector to support effective international communication and enhance service quality at airports, aligning with ICAO standards.